SOSIALISASI DAN PELATIHAN SAFETY HOUSE PADA WARGA DI RT 04 RW 13 KELURAHAN TANJUNG RIAU KOTA BATAM - Sri Zetli; Pastima Simanjuntak; Erlin Elisa; Koko Handoko; Neni Marlina Br Purba (ASOSIASI IDEBAHASA KEPRI, 2026)
Occupational Safety and Health (OSH) is not only important in industrial or office environments, but also in households that have the potential for accidents and health problems. One group that is vulnerable to these risks is housewives, who carry out daily activities at home. The lack of understanding of safety principles at home (safety house) has the potential to cause accidents, such as burns while cooking, slipping while washing, or exposure to household cleaning chemicals. This Community Service Activity (PKM) was carried out in RT 04 RW 13, Tanjung Riau Village, with the aim of increasing housewives' knowledge and awareness regarding the implementation of K3 at home. The methods used were socialization, interactive counseling, and group discussions on the concept of safety house and practices for preventing household accidents. The results of the activity showed an increase in participants' understanding of the importance of risk management at home, as demonstrated by increased enthusiasm, critical questions, and awareness to apply simple preventive measures in daily activities. Thus, this program made a real contribution to building a culture of safety at the household level, especially for housewives as the front line in maintaining the safety and health of their families.